Implementasi CSR Perusahaan MIGAS dalam pelayanan kesejahteraan Masyarakat di Tuban (study implementasi CSR Joint Operating Body Pertamina Petrochina East Java) - Muhammad Miftahul Huda (Asketik : Jurnal Agama dan Perubahan Sosial, 2019)
This paper is a result of research study about the impact of Corporate Social Responsibility (CSR) of oil and gas company in social welfare. This research specifically focus on communities in five villages around an oil and gas Joint Operating Body managed by Pertamina and Petrochina of East Java operating in Tuban Regency, East Java Province. The company performed CSR as required by Law No.22 Year 2001 on Oil and Gas which further elaborated by Special Task Force for Upstream Oil and Gas Business Activities' (SKK Migas) Regulation No. 017/PTK/III/2005 on Guidelines for Community Development. The research method is a qualitative and descriptive. The research found that the company's CSR implemented four programs which do not led to a good practice of community development. Many programs implemented did not align with community needs, lacking of transparency – which then led to misuse of fund, and no impact on affected communities' welfare. Poverty in natural resource rich area is a common phenomena known as as the 'resource course'. It is called a 'curse' as the natural resources were supposed to be a blessing for a prosper and prosperous community. However, the opposite is often happen. This resource curse is believed can be solved by many things, in which one of them, is the company's role through Corporate Social Responsibility (CSR). In order for CSR programs to work well, align with community needs and have a sustainable impact, then the management of CSR becomes an important thing to be pushed. Transparency and accountability of CSR programs are crucial points which required to be monitored by stakeholders. CSR is not a charity based on voluntary action, but an obligation that is the responsibility of the company as good mining practices.